Tuberculosis: insights into latency, treatment strategies, and the potential roles of metronidazole - Wiker, Harald G. (Frontiers in Tuberculosis, 2023)
Recent studies challenge the traditional belief that latent tuberculosis is a lifelong condition. Analysis of tuberculosis decline in low endemic areas suggests that latency is diminishing, and a significant proportion of individuals likely clear the infection each year. The risk of developing active tuberculosis diminishes over time, highlighting the importance of early intervention for optimal treatment outcomes. The global estimate of latent tuberculosis infection has been revised to approximately 23% of the global population. Latent bacilli undergo mutation and proliferation, contrary to the previous notion of dormancy. Treatment regimens for tuberculosis, particularly multidrug-resistant strains, have improved with the BPaLM regimen. However, current treatment approaches for drug sensitive tuberculosis do not specifically target dormant bacilli, necessitating the development of better protocols. Metronidazole shows potential in killing nonproliferating Mycobacterium tuberculosis, but its clinical effectiveness remains uncertain. Adverse effects and drug interactions of metronidazole should be considered. Alternative treatment options and the role of lung flora in tuberculosis therapy require further investigation. The suitability of metronidazole for this purpose remains open.